Low Molecular Weight Supramolecular Allobetuline-, Cyclohexanol-, or Undecanol-Appended 1,2,3-Triazole-Based Gelators: Synthesis and Molecular Dynamics Simulation Study - Lipson, Victoria; Zhikol, Oleg; Shishkina, Svetlana; Semenenko, Alexander; Kulyk, Karina; Mateychenko, Pavel; Musatov, Vladimir; Mazepa, Alexander; Vakula, Vladimir; Borisov, Alexander; Kyrychenko, Alexander (SynOpen, 2023)
Three novel isomeric supramolecular allobetuline-appended 1,2,3-triazole-based potential gelators and two model compounds with cyclohexanol or undecanol fragments in the structure instead of the triterpenoid platform were synthesized. Their ability to form gels in different solvents was studied experimentally and computationally by molecular dynamics simulations and quantum chemical calculations. We found that the gelling ability of such compounds is driven by the binding energy of intermolecular tail substituent interactions. The less significant factor is the molecule unfolding in a solvent, providing that the gelling substance is actually soluble. Preferred unfolded conformations were identified by classical molecular dynamics simulation and suggested the most prospective 1,2,3-triazole-based potential gelators.
Keywords: allobetuline; cyclohexanol; undecanol; supramolecular 1,2,3-triazole-based gelators; click reaction; molecular dynamics simulation; low-molecular-weight organogelator